Tactics of Earthy Data: Decolonising for the Anthropocene - U+16DE, diane (Technology and Regulation, 2024)
This article presents that decolonizing cannot happen without acknowledging the role of land relations in constituting data and radically reconstituting what we are governing when we claim to govern ‘data.’ To this end, it reflects upon how the juxtaposition of the ‘data colonialism’ and the ‘Anthropocene’ discourses can be productive by highlighting their common settler colonial impulses in understanding the categories of the ‘material’ and the ‘epistemological’ as distinctive. Next, the article draws upon the Place-Thought framework proposed by Anishinaabe-Haudenosaunee scholar Vanessa Watts and others to argue that in addition to being a demand for giving land titles to Indigenous peoples, #LandBack movements should be understood as a decolonizing call for realizing the seamless coherence of the material-epistemological, both outside and within Europe. The last section proposes earthy data as decolonizing tactics against the settler understandings of data.